Effects of Laparoscopic Ovarian Drilling on Restoration of Menstrual Cycles, Hormonal Profiles and Pregnancy Rate in Women with Polycystic Ovary Syndrome - Shelan Omar Jaafar1, Ghada Saadulla Alsakkal2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
One of the major cause of an ovulatory infertility is polycystic ovary syndrome with a multifactorial etiology.Laparoscopic ovarian drilling (LOD) is regarded as the method of choice for inducing ovulation in those notresponding to oral ovulation induction with PCOS.A prospective study was carried out for assessment of effects of LOD on menstruation, serum levels ofhormones, and reproductive outcome including ovulation and pregnancy rate.A total of 169 patients with an ovulatory infertility underwent LOD over a period of about two years. Allpatients assessed three times for clinical characteristics and serum hormone levels LH, FSH, testosterone,SHBG, prolactin and AMH. FAI and LH/FSH ratio calculated, first before the procedure, second within oneweek after and the last one after three months with the ovulation and pregnancy outcome follow up until sixmonth.The prevalence of irregular menstrual pattern was 89.3%, significantly (P< 0.001) decreased to 19.5%after the procedure with improvement of hirsutism, acne and scalp hair loss, there was a highly significantdecrease in the serum levels of LH, testosterone, AMH, FAI and LH/FSH ratio (P ? 0.001) and a highlysignificant elevation of serum SHBG and prolactin post-operatively, resumption of spontaneous ovulationof 56.2%, and the pregnancy rate of all the study group was 26%. In conclusion, LOD regarded as a methodfor improvement of the hormones, restoration of menstruation and increasing ovulation and pregnancy rate.